In Search of the Two-Handed Economist Ideology, Methodology and Marketing in Economics - Freedman, Craig; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
For the economics profession, issues of marketing and ideology have often been reduced to the status of 'the love that dare not speak its name'. This volume brings these issues out of the closet and examines what effect, if any, these factors have in shaping the contours of the discipline. The way in which economists face policy issues is in part driven, even if only subconsciously, by unacknowledged ideological concerns and the increasing need to sell one's theories, views and policies in a frustratingly competitive academic market. In seven carefully and provocatively granulated chapters, the volume raises possible implications of these marketing and ideological imperatives by approaching the problem from a number of surprising and irreverent directions. Though unfortunately, in its irrevocable denouement the text proves incapable of creating anything resembling a life changing experience let alone coming to any definite and irrefutable conclusions. Like life itself, economics is full of uncertainties and uncontrollable difficulties.
Prologue: Marketing Truth -- 1. Elephant Stalkers: Fixed Perspectives and Required Results -- 2. A Tale of Two Cities: A Priori Assumptions and A Priori Conclusions -- 3. The Heart is a Lonely Hunter: Chicago's Climb to Glory -- 4. Love among the Ruins: Understanding The Romantic Economist: Imagination in Economics -- 5. The Chicago School of Anti-Monopolistic Competition: Stigler's Scorched Earth Campaign againt Chamberlin -- 6. De Gustibus Non Est Diputandum: George Stigler through Gary Becker's Eyes -- 7. Marching to a Different Drummer: Sam Peltzman Discusses George Stigler.
Keywords: Economic policy; Marketing; History of Economic Thought/Methodology.